The prognostic role of beta-cetenin in patients with advanced stage serous ovarian cancer - Aluloski Igor; Petrushevska Gordana; Jovanovic Rubens; Tanturovski Mile (Македонско лекарско друштво = Macedonian medical association, 2017)
Serous ovarian cancer is the most common sub-type of epithelial ovarian cancer and is the leading cause of cancer-related death among gynecologic cancer patients. Beta-catenin plays a vital role in the genesis of certain types of cancer. Its implications in the survival and prognosis of patients with serous ovarian cancer is not yet fully understood. We conducted immunohistochemical analysis in tumor specimens from 40 patients to determine the expression of beta-catenin. We analyzed the relationship between beta-catenin expression and the FIGO disease stage and the tumor grade. We used Kaplan Meier statistics to analyze the prognosis. We detected increased expression of beta-cateinin in patients with FIGO Stage III or IV (p=0.0003). We did not detect a statistically significant association between beta-catenin expression and tumor grade (p=0.817). The positive expression of beta-catenin was associated with shorter average survival (p=0,034). There was no statistically significant relationship between beta-catenin expression and other patho-histhological tumor features. Beta-catenin expression is associated with poorer prognosis in patients with serous ovarian cancer
B-катенинот и неговата прогностичка улога кај пациентки со напреднат стадиум на серозен оваријален карцином
Keywords: ovarian cancer; beta-catenin